A Biomechanical Perspective on Distal Radioulnar Joint Instability - Omokawa, Shohei; Iida, Akio; Kawamura, Kenji; Nakanishi, Yasuaki; Shimizu, Takamasa; Kira, Tsutomu; Onishi, Tadanobu; Hayami, Naoki; Tanaka, Yasuhito (Journal of Wrist Surgery, 2017)
Background The purpose of this article was to review the anatomy, kinematics of the distal radioulnar joint (DRUJ), and to discuss definition, classification, and diagnosis of DRUJ instability.Methods A biomechanical perspective on physical examination of DRUJ ballottement test was documented. Physiological dynamic DRUJ translation and differences of the translation following sequential ligament sectioning and changes in different forearm and wrist positions were demonstrated. The clinical significance of each ligament's contribution to joint stability in specific wrist positions was addressed.Conclusion Each ligament stabilizing the DRUJ contributed to joint stability depending on the direction (palmer or dorsal) and different positions of the wrist and forearm. DRUJ ballottement test in each wrist and forearm position may detect tears of specific ligament stabilizing the DRUJ.
Keywords: DRUJ; TFCC; biomechanics; anatomy; function